How we got to now : six innovations that made the modern world - Keenan, Sheila (Viking, 2018)
Explores the history and effects of six inventions--glass, refrigeration, sound, sanitation, time, and light-- that have helped shape modern society. Adapted from the original text by Steven Johnson to appeal to younger readers.